Study relationship of the length and the weight of Baderbang fish (Barbodes schwanenfeldii) in The Dempok river, Gampingan, Pagak Sub-District, Malang Regency, East Java - Ganjar Adhywirawan Sutarjo; Riza Rahman Hakim; Alisatul Amalia (Universitas Muhammadiyah Malang, 2022)
Baderbang fish (Barbonymus schwanenfeldii) is one of Indonesia's endemic fish which has a great opportunity to be cultivated as consumption fish. The success of fish farming is supported by information about the growth patterns in the area of ​​origin of the fish. The study of the relationship between fish length and weight is one indicator to determine the growth pattern of Baderbang fish (Barbonymus schwanenfeldii). This research was conducted with the aim of knowing the morphometrics and growth patterns of Baderbang fish in the Dempok river, in the side of the Pagak village, Malang district. The data analysis was performed, namely the LAM (Liner Allometric Method) data analysis. This model was used to determine the values ​​of a and b. Baderbang fish regression for 6 months is in the range of 1.0558-3.1947, this shows that the growth pattern of Baderbang fish varies every month which includes an isometric growth pattern which is a parallel growth pattern between length increase and increase, growth pattern Positive allometric is a growth pattern with weight gain faster than length gain, while negative allometric growth is a growth pattern with a faster increase in length than weight gain. The long-weight relationship of fish in the Dempok river flow has R2 results ranging from 0.2079-0.9409.